How long until there are detrimental effects from bacterial meningitis with delayed antibiotics?. Issue 7 (July 2016) - Watson, Mark; Yang, Davis
Abstract : Evidence‐Based Answer : The risk of death and neurological sequelae from bacterial meningitis is increased if antibiotics are delayed more than 6 hours after arrival in the emergency department (ED) and more than 3 hours after admission. The risk of death appears to increase with each hour of delay (SOR: C, based on several case series).